Exports, capabilities, and industrial policy in India - Jesus Felipe; Utsav Kumar; Arnelyn Abdon (Levy Economics Institute of Bard College, 2010)
An extensive literature argues that India's manufacturing sector has underperformed, and that the country has failed to industrialize; in particular, it has failed to take advantage of its laborabundant comparative advantage. India's manufacturing sector is smaller as a share of GDP than that of East Asian countries, even after controlling for GDP per capita. Hence, its contribution to overall GDP growth is modest. Without greater participation of the secondary sector, the argument goes, the country will not be able to develop and become a modern economy. Standard arguments blame the license-permit raj, the small-scale industrial policy, and the supposedly stringent laws. All these were part of the industrial policy regime instituted after independence, which favored the heavy-machinery subsector. We show that this policy bias negatively affected the development of India's labor-intensive sector, as the country should export with comparative advantage a larger number of these products, given its income per capita. However, India's manufacturing sector is relatively well diversified and sophisticated, given also the country's income per capita. In particular, India's inroads into machinery, metals, chemicals, and other capital- and skilled labor-intensive products has allowed the country to accumulate a large number of capabilities. This positions India well to expand its exports of other sophisticated products.
Keywords: O20; O25; O53; 330; capabilities; diversification; India; industrial policy; revealed comparative advantage; sophistication